Relationship between final performance and block times with the traditional and the new starting platforms with a back plate in international swimming championship 50-m and 100-m freestyle events - Garcia-Hermoso, A.; Escalante, Y.; Arellano, R.; Navarro, F.; Dominguez, A. M.; Saavedra, J. M. (Journal of Sports Science & Medicine, 2013)
The purpose of this study was to investigate the association between block time and final performance for each sex in 50-m and 100-m individual freestyle, distinguishing between classification (1st to 3rd, 4th to 8th, 9th to 16th) and type of starting platform (old and new) in international competitions. Twenty-six international competitions covering a 13-year period (2000-2012) were analysed retrospectively. The data corresponded to a total of 1657 swimmers' competition histories. A two-way ANOVA (sex × classification) was performed for each event and starting platform with the Bonferroni post-hoc test, and another two-way ANOVA for sex and starting platform (sex × starting platform). Pearson's simple correlation coefficient was used to determine correlations between the block time and the final performance. Finally, a simple linear regression analysis was done between the final time and the block time for each sex and platform. The men had shorter starting block times than the women in both events and from both platforms. For 50-m event, medalists had shorter block times than semi- finalists with the old starting platforms. Block times were directly related to performance with the old starting platforms. With the new starting platforms, however, the relationship was inverse, notably in the women's 50-m event. The block time was related for final performance in the men's 50- m event with the old starting platform, but with the new platform it was critical only for the women's 50-m event.